Corporate purpose, CSR, and ESG a trans-atlantic perspective - Binder, Jens-Hinrich 1974-; Hopt, Klaus J. 1940-; Kuntz, Thilo 1977- (Oxford University Press, 2024)
"In recent years, the longstanding debate between shareholder-oriented and stakeholder-oriented models of corporate governance for large listed, or 'public' corporations, has experienced a resurgence. Simultaneously, a wave of new regulations has reshaped the legal landscape, compelling businesses to integrate public objectives - such as environmental protection or the social interests of specific stakeholder groups - into their decision-making processes, which were traditionally driven solely by profitability considerations. Against this background, the book brings together economic, comparative, historical, and doctrinal perspectives of scholars from US and European legal academia."
Keywords: Rechtsvergleich; Corporate Social Responsibility; Nachhaltigkeit; Europa; USA; Corporate governance; Social responsibility of business